Influence of Physical and Chemical Soil Properties on the Adsorption of Escherichia coli in Mollisols and Alfisols of Argentina - Behrends Kraemer, Filipe B. (2013)
Fil: Behrends Kraemer, Filipe B. Universidad de Buenos Aires. Facultad de Agronomia. Departamento de Ingenieria Agricola y Uso de la Tierra. Cátedra de Manejo y Conservación de Suelo; Argentina.